PENINGKATAN PERILAKU PEDULI HUKUM DAN LINGKUNGAN MELALUI PROGRAM KEMITRAAN MASYARAKAT PEDULI HUKUM - Kamarullah; Nafsiatun; Muhammad Irfani Hendri; Ari Widiyantoro (Universitas Lancang Kuning, 2019)
Law enforcement requires firm assertiveness and public awareness. Law enforcement will guarantee the life of a safe nation and state. Communities need high legal awareness so that they have high legal behavior. The province of West Kalimantan is one of the provinces that experiences land and forest fires every year. Factors of land and forest fires include natural and human factors. Natural factors, especially the dry season is a difficult factor to control, so one of the preventive steps is to control human factors. Control of human factors through increasing the care of law and the environment so that humans do not violate the law, especially the burning of land and forests. The Community Care Law Partnership Program (PKM) is one way to improve legal and environmental care behavior. The method for implementing PKM activities was through socialization and counseling, demonstrations and training, and assistance to partners, namely the people of Rasau Jaya III village, including farmers, PKK women and youth groups. The results of the activity showed that the Rasau Jaya III village officials and the community were enthusiastic in following this activity. The activity was carried out on the sidelines of the busy work of the people of Rasau Jaya III village. Activities are carried out with a persuasive approach so that interaction with the community becomes comfortable. This is done so that the transfer of knowledge and skills goes well. Based on the results of the questionnaire before and after the activity showed that the law and environment care behavior of the community of Rasau Jaya III increased. This condition is very important to create law enforcement and environmental care for a comfortable human life.